Application of lung volume reduction surgery for a child with filamin A (FLNA) mutations. Issue 1 (4th October 2021) - Burrage, Lindsay C.; Heinle, Jeffrey S.; Cerfolio, Robert H.; Guillerman, Robert P.; Patel, Kalyani R.; Santiago, Nahir C.; Hoover, Wynton C.; Mallory, George B.
Abstract: Diffuse lung disease in early childhood due to mutations in the filamin A gene has been recently reported. Clinical outcomes vary among individuals indicating variability in phenotype but a substantial proportion of reported cases in early life have ended up in death or lung transplantation. We recently encountered a school‐aged child in whom the diagnosis of a filamin A mutation was delayed and the natural history of emphysematous lung disease was altered by serial lung volume reduction surgeries. She eventually underwent a bilateral lung transplant and we report the natural history of her disease and treatments applied herein.